Pengaruh Transformasi Digital Layanan dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Perumda Tirta Kanjuruhan Kabupaten Malang - Shella Rila Octavianti; Sanita Dhakirah; Yosi Afandi (INDO PUBLISHING, 2026)
Digital service transformation and service quality improvements are the primary strategies of Perumda Tirta Kanjuruhan, Malang Regency, to enhance customer satisfaction. However, satisfaction growth has slowed down, creating a gap between efforts and results. This study aims to analyze the effect of digital service transformation and service quality on customer satisfaction, both partially and simultaneously. This research utilizes a quantitative method with an explanatory research approach involving 100 respondents. The sample was determined using a purposive sampling technique, targeting active customers for at least the last six months. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results indicate that the coefficient of determination is 48.8%, while the remaining 51.2% is influenced by other variables outside this study. Empirically, the research proves that digital service transformation and service quality, both partially and simultaneously, have a positive and significant effect on customer satisfaction. Service quality is proven to have the most dominant influence compared to digital transformation. Therefore, Perumda Tirta Kanjuruhan is advised to continuously improve the standards of direct employee service quality and further optimize the functionality of digital service features to ensure sustainable customer satisfaction.